Updates on aspects of Gossipiboma: An integrative literature review (Research, Society and Development, 2024)
The term gossypiboma refers to a surgical complication due to the unintentional forgetting of surgical material, such as compresses or gauze, in the body cavity post-procedure. The incidence is higher in the abdominal cavity, pelvis and chest, especially in gynecological surgeries, such as cesarean sections. The objective of the present study is to evaluate the cases of gossypiboma described in the literature regarding epidemiological aspects, clinical picture, main sites of involvement, diagnostic tests, complications and forms of prevention. Methodology: This is an integrative review that used data from the Virtual Health Library (VHL), Elsevier, Scientific Electronic Library Online (SciELO) and National Library of Medicine (PubMed) databases, and crossed the descriptors "Gossipiboma ", "Epidemiology", "Treatment" and "Complications". Results: A total of 20 cases were addressed, with a greater incidence being observed in women. Emergency procedures confirmed to be a risk factor. The clinical picture was nonspecific, varying depending on where the material was forgotten. Perforations and fistulas were observed complications. Discussion: Computed tomography was the most used method for diagnosing gossypibomas, although there is no pathognomonic finding in any method. The formation of fistulas is associated with the aseptic process and the residence time of the material. The average time to diagnosis was 9.5 years, similar to other studies analyzed. Conclusion: Gossipibomas correspond to a medical error subject to medico-legal penalties. Counting and the use of radiopaque gauze are essential, since diagnosis is difficult due to the nonspecific clinical picture.